O ensino na área da saúde envolve a interseção de duas grandes áreas de conhecimento - educação e saúde - Bahia, Silvia Helena Arias [UNIFESP] (2016)
Introduction: The teaching in health education area in undergraduate and graduate levels, involves the intersection between two major areas of knowledge, the education and the health, both are constituted in the networks of the social, culture, institutional, economic and political. From 2003, the training and the teaching in health took a prominent role in the context of education and health policies, in order to ensure qualified training to health professionals and contribute to a resolutely and better health care. In this sense, inducing initiatives were implemented, among which the Pro-Education in Health, which was established collaboratively in 2010 by the Ministry of Health (MOH), in partnership with the Ministry of Education (MEC) and CAPES. Objective: To understand the inducer potential of the Pro-Education in Health, from the in a perspective of a training policy in the stricto sensu level, and of development of research on teaching in health. Methods: The study used mixed methods through the integration of quantitative and qualitative, through the methodological integration model dialogical type, being built in view of the triangulation of data, carried out from 2011 to 2016. The production data understood documentary analysis of the 31 projects included in the Notice 24/2010 and semi-structured interviews with 17 project coordinators. The data analysis was undertaken from the content analysis, of the thematic type. Results: The analysis of projects identifies that within the areas of CAPES evaluation, the Health Sciences was the Great predominant area, highlighting the medical and nursing majors, among the areas of knowledge. It was observed that the subject area, "The training and development of teacher in health" was the most interest; and the lower demand were the "teaching management in health," and the "integration between health, education, science, and technology policies". The South and Southeast regions concentrated the largest number of projects, covering 32 institutions and 59 Graduate Programs. It was conducted subjective analysis of 395 titles of research developed. The recurring terms were training and evaluation, and of less quotation was management. The analysis of the documents and of the voices of interviewed made possible to characterize the potential of the Pro-Education in Health on three main themes: the training, the research and the policy. In the context of thematic, the training in the Pro-Health Education emerge two categories: responses to the demand for education and training paths. The second theme that emerges from the potential of the Pro-Education in Health is the research, identifying two categories: (1) interfaces between the lines of research focus area and the objects of study and (2) the challenges for recognition the scientific area. The third thematic relates to the policy: 19 higher education institutions participants of the Pro-Education in Health has established and / or developed partnership with programs and policies, among which stands out the adherence to the Education Programs at Work in Health (Pet- health) and Reorientation National Program for Professional Training in health (Pro-health). The Difficulties or critical problems identified in the development of the projects are directed to issues of institutional relations and resource management: Link of the Project to the Graduate Program, use of resources, operational support, program coordination and (lack of) knowledge of institutional peers. The strengths of the research focus are the perspective of the coordinators, financing, institutional partnerships and the formation of collaborative networks. With regard to partnerships with the service recorded the desire to strengthen relations, assuming that exist much to build, as also emphasized the importance of establishing research networks and the scope of the connections that they make possible. Conclusions: Pro-Education in Health strengthened the qualified training process and teaching in health research, in the hope that they may carry out changes in the academy and the health service daily. In this context, it is assumed that the Pro-Education in Health as an inducer policy by developing collaborative networks and the production of knowledge, but also confronted with the challenge to establish itself as an effective constituent of a public policy formation and health work.